Prevalence of Anthracycline Induced Cardiomyopathy amongst Cancer Patients Treated at Tertiary Teaching and Refferal Hospital in Nairobi Kenya - C.N, Tonio; E.N, Ogola; N.A, Abinya; E M, Karari; B, Gitura; A.O, Odhiambo (International Journal of Scientific Research and Management (IJSRM), 2019)
Background: Cardiovascular complication is a major consequence of cancer treatment. Anthracycline induced cardiomyopathy is a known cause of long term morbidity and mortality among cancer survivors. The burden of this complication is unknown in our settingObjective: This study aimed to determine the prevalence of cardiomyopathy in ambulatory patients treated with anthracycline (Ac) containing chemotherapy at Kenyatta National Hospital (KNH) as measured by two dimensional (2D) echocardiography (ECHO).Study design: A hospital based inpatient/outpatient cross sectional, descriptive study.Study setting: This study was carried out in various outpatient clinics and oncology wards in Kenyatta National Hospital. These included the adult hematooncology clinic 23, Ground floor C (GF-C), Ward 8C and Ground floor D (GF-D)Subjects: The study population included patients who have been exposed to Ac. The minimum Ac dose was 200mg/m2. A total of 129 patients with various types of cancers were sampled consecutively over a period of 3 months. Eligible patients underwent a 2D ECHO and left ventricular ejection fraction (LVEF) was assessed.Results: Patients between the ages of 15 and 75 participated in the study, the mean age was 45.6 years, with the female to male ratio of 4.3:1. Majority of the patients had breast cancer (67.4%) and the treatment regimen in over 65% of them was doxorubicin and cyclophospomide (AC). The mean cumulative dose was 236mg/m2. All patients recruited had received a cumulative dose of between 200 - 450mg/m2. Most of the patients (63%) had completed Ac within one year of their cardiac evaluation. Only 14.0 % of the patients had a pretreatment ECHO. The overall prevalence of LV systolic dysfunction detected by echocardiography was 3.1% (95% CI 0.9– 7.8). The study was not powered to make associations with age, sex and cumulative dose and presence of cardiomyopathy.Conclusions: The study demonstrates a prevalence of 3.1% cardiomyopathy among cancer patients treated with anthracyclines. This figure is comparable to similar studies done. The prevalence described in most studies ranges from between 1% to 20.5%.Anthar